FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN TEMPAT PERSALINAN DI WILAYAH KERJA PUSTU MUMPA TAHUN 2019 - Nana Mardiana; Sandra Harianis (STIKES HUSADA GEMILANG, 2020)
Standardized childbirth services are childbirth services by midwives, doctors or obstetric specialists who work in health facilities and are carried out in health facilities. In 2017 the target of achieving childbirth in health facilities of Salak River Health Center is 100%, while the achievement of Mumpa village is only 68.1%. Labor assistance carried out at home and helped by baby shamans is still done by the local community so that it can cause complications that will be difficult to handle. The purpose of this study is to find out the factors related to the selection of birth places in the Auxiliary health center of Mumpa in 2019. This research is quantitative using cross sectional design. This study was conducted in Mumpa village on July 8-13, 2019 with a population of 82 people and sampling techniques using Purposive Sampling so that a sample of 54 respondents was obtained. Analysis of bivariate test data using Chi Square obtained results from 5 factors studied, there are 4 factors related to the selection of places of delivery, namely the Labor Helper factor (P = 0,000), Knowledge (P = 0.020), Culture (P = 0.039) and P4K (P = 0.002). While there is 1 factor that is not related to the selection of the place of delivery, namely Health Insurance (P = 0.239). This research is expected to be an input for counseling in increasing the coverage of childbirth in health facilities.